Integrasi Literasi Digital dalam Kurikulum PAI: Tantangan dan Peluang bagi Guru di Sekolah Dasar Islam Terpadu - Muh. Fauzi; Ariyogo Adi‎ Guna; Zulfani Sesmiarni; Syahrur Ramli; Merri Yelliza (WISE Pendidikan Indonesia, 2026)
This study aims to analyze the challenges and opportunities for integrating digital literacy into the Islamic Religious Education (PAI) curriculum at Integrated Islamic Elementary Schools (SDIT). Amidst the massive digital transformation, PAI teachers face pressure to adopt technology without compromising spiritual values. The research methodology used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and curriculum documentation studies at SDIT. The results of the study indicate that digital literacy integration is still at the media substitution stage, where technology is used as a presentation aid but has not yet touched on a deep pedagogical transformation. The main challenges include the technological competency gap between generations of teachers, the limited digital content that is in accordance with Islamic beliefs for elementary school children, and sociocultural concerns about the negative impacts of the internet. However, this study also found significant opportunities in the use of gamification and digital portfolios that have been proven to increase student learning motivation by forty percent. The study's conclusion confirms that successful digital literacy integration requires curriculum restructuring that instills